The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.3758/bf03337328
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mothers’ eating restraint and their children’s attitudes and behaviors

Abstract: Dieting practices and beliefs offourth-grade children and their mothers were studied. The children's self-esteem, locus of control, and eating restraint were also assessed. Fifty children and their mothers were administered an eating restraint scale. The children were also administered self-esteem and locus of control scales. Although the children's eating restraint, self-esteem, and locus of control were not related, the mothers' eating restraint was found to be positively related to their daughters' eating r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…Previous studies in adults have reported correlations between actual and reported height and weights that typically range between 0.96 and 0.99 [36,37]. Parental BMI was categorized as underweight (BMI \18.5), normal (BMI 18.5-24.9), overweight (BMI [25) and obesity (BMI [30).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in adults have reported correlations between actual and reported height and weights that typically range between 0.96 and 0.99 [36,37]. Parental BMI was categorized as underweight (BMI \18.5), normal (BMI 18.5-24.9), overweight (BMI [25) and obesity (BMI [30).…”
Section: Measurementsmentioning
confidence: 99%
“…There have also been reports suggesting that the risk of becoming obese in young adulthood is three-to fivefold higher if either the mother or father is obese compared with the parent not being obese [6,20,23]. However, other findings suggest that parental behaviors shape many aspects of a child's development; as such, a parent's diet history and eating habits would influence the development of children's eating behaviors and weight outcomes [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Even though it has been identified that the mother has a fundamental role in education and transmission [3], family, friends, school and media influence children's eating behavior [4] suggesting that the most important role is on parental behaviors as they shape many aspects of children's development, eating concerns and weight outcomes [5,6] as such, intervening early may be necessary to engender healthy behaviors before malnutrition patterns are established [7].…”
Section: Introductionmentioning
confidence: 99%
“…In two studies, mothers' dieting or weight concerns were associated with adolescent (Pike & Rodin, 1991) and grade 4 (Ruther & Richman, 1993) daughters' individual weight concerns. However, three other studies found no significant relationship between mother and daughter eating concerns when studying adolescents (Attie & Brooks-Gunn, 1989;Moreno & Cooke, 1994;Thelen & Cormier, 1995).…”
mentioning
confidence: 99%